Art Therapy on Stress and Anxiety of Chronic Kidney Failure (CRF) Patients with Hemodialysis in Bogor City Hospital - Nieniek Ritianingsih; Farial Nurhayati; Amid Salmid (GLOBAL HEALTH SCIENCE GROUP, 2022)
Chronic kidney disease includes conditions that damage the kidneys and decrease their ability to keep them healthy to do work. In addition to physical complaints experienced by someone with kidney failure, many psychosocial complaints are also found such as sadness, anxiety, fear, and even feelings of helplessness due to suffering from an illness. The current state of the COVID-19 pandemic causes increased stress and anxiety in the community. One of the nursing actions in overcoming stress and anxiety in patients with kidney failure is Art Therapy. Objective to determine the effect of art therapy on the anxiety of chronic kidney failure patients with hemodialysis at the Bogor City Hospital. Methods: This research is a quantitative study using a quasi-experimental method with a pre post test approach with control group design. There is a difference in pre stress scores and post stress scores in the intervention group (p value 0.001). There is a difference in pre anxiety scores and post anxiety scores in the intervention group (p value 0.001). There is a significant difference between the stress score of the control group and the stress score of the intervention group after performing art therapy (0.031). There was a significant difference between the anxiety scores of the control group and the anxiety scores of the intervention group after performing art therapy (p value 0.001). Art therapy is effective for chronic kidney failure patients who experience stress and anxiety. Nurses can use this therapy to provide psychosocial nursing care.